2019
DOI: 10.1177/0333102419876909
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring chronic headache and medication-overuse headache prevalence in Denmark

Abstract: Objectives To study chronic headache and medication-overuse headache (MOH) prevalence; to identify groups with high prevalence of these conditions; and to identify the most frequently used pain medications among respondents with chronic headache. Background Chronic headache and MOH prevalence in Denmark were last estimated in 2010. Methods In this cross-sectional study, 104,950 individuals aged ≥16 years were randomly sampled for the 2017 Danish Capital Region Health Survey. Responses to questions about headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 58 publications
2
38
1
Order By: Relevance
“…Conceivably, individuals who at baseline in HUNT2 already had experienced that alcohol causes headache may tend to avoid it [28]. In previous prospective HUNT studies, we have found that physical activity gave lower risk of headache and migraine compared to physical inactivity [25,32]. Contrary to these results, in the present study physical inactivity was associated with lower risk of having stable headache.…”
Section: Risk Factorscontrasting
confidence: 99%
See 2 more Smart Citations
“…Conceivably, individuals who at baseline in HUNT2 already had experienced that alcohol causes headache may tend to avoid it [28]. In previous prospective HUNT studies, we have found that physical activity gave lower risk of headache and migraine compared to physical inactivity [25,32]. Contrary to these results, in the present study physical inactivity was associated with lower risk of having stable headache.…”
Section: Risk Factorscontrasting
confidence: 99%
“…More speculatively, the difference could also in part be related to differences in prescription of analgesics and/or genetic, psychosocial, behavioral factors and ethnicity. Among participants in the HUNT studies, there is a relatively low proportion of immigrants [16], whereas in the Danish study the highest MOH prevalence was found among non-Danish, non-western participants [25].…”
Section: Time Trendsmentioning
confidence: 75%
See 1 more Smart Citation
“…The prevalence of MOH is estimated between 1% and 3%, making it one of the most common secondary headache disorders 12‐16 . In tertiary headache clinics, about 50% of patients also have medication overuse 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Cephalalgia, Westergaard et al present an epidemiological study of medication overuse headache (MOH) in Denmark. The authors used the results of a 2017 survey of 104,950 Danish adults to update estimates of the prevalence of chronic headache (CH) and MOH in Denmark, and to identify the most commonly overused medications (2). The response rate was modest, at 52.6%, but weighting techniques were used to compensate for the potential effects of differential non-response.…”
mentioning
confidence: 99%